WebGL insights - Cozzi, Patrick (CRC Press, Taylor & Francis Group, 2016)
Given its ubiquity, plugin-free deployment, and ease of development, the adoption of WebGL is on the rise. Skilled WebGL developers provide organizations with the ability to develop and implement efficient and robust solutions-creating a growing demand for skilled WebGL developers. WebGL Insights shares experience-backed lessons learned by the WebGL community. It presents proven techniques that will be helpful to both intermediate and advanced WebGL developers. By focusing on current and emerging techniques, the book demonstrates the breadth and depth of WebGL